Demographics of Pediatric OHCA Survivors With Postdischarge Diseases: A National Population-Based Follow-Up Study - Lee, Tsung-Han; Juan, I-Cheng; Hsu, Hsiu-Ying; Chen, Wen-Liang; Huang, Cheng-Chieh; Yang, Mei-Chueh; Lei, Wei-Yuan; Lin, Chih-Ming; Chou, Chu-Chung; Chang, Chin-Fu; Lin, Yan-Ren (Frontiers in Pediatrics, 2020)
Background: Postdischarge diseases (PDDs) have been reported for adult survivors of out-of-hospital cardiac arrest (OHCA). However, the detailed demographics of pediatric OHCA survivors with PDDs are not well-documented, and information regarding functional survivors is particularly limited. We aimed to report detailed information on the PDDs of survivors of traumatic and non-traumatic pediatric OHCA using a national healthcare database. Methods: We retrospectively obtained data from the Taiwan government healthcare database (2011–2015). Information on the demographics of traumatic and non-traumatic pediatric OHCA survivors (<20 years) was obtained and reported. The patients who survived to discharge (survivors) and those classified as functional survivors were followed up for 1 year for the analysis of newly diagnosed PDDs. The time from discharge to PDD diagnosis was also reported. Results: A total of 2,178 non-traumatic and 288 traumatic OHCA pediatric cases were included. Among the non-traumatic OHCA survivors (n = 374, survival rate = 17.2%), respiratory tract (n = 270, 72.2%), gastrointestinal (n = 187, 50.0%), and neurological diseases (n = 167, 49.1%) were the three most common PDD categories, and in these three categories, the majority of PDDs were atypical/influenza pneumonia, non-infective acute gastroenteritis, and generalized/status epilepsy, respectively. Among the traumatic OHCA survivors (n = 21, survival rate = 7.3%), respiratory tract diseases (n = 17, 81.0%) were the most common, followed by skin or soft tissue (n = 14, 66.7%) diseases. Most functional survivors still suffered from neurological and respiratory tract diseases. Most PDDs, except for skin or soft tissue diseases, were newly diagnosed within the first 3 months after discharge. Conclusions: Respiratory tract (pneumonia), neurological (epilepsy), and skin or soft tissue (dermatitis) diseases were very common among both non-traumatic and traumatic OHCA survivors. More importantly, most PDDs, except for skin or soft tissue diseases, were newly diagnosed within the first 3 months after discharge.